Simulating the long‐term impacts of drainage and restoration on the ecohydrology of peatlands. Issue 8 (4th August 2017) - Young, Dylan M.; Baird, Andy J.; Morris, Paul J.; Holden, Joseph
Abstract: Drainage alters the carbon storage and accumulation functions of peatlands, but the long‐term effects of drainage ditches, and their restoration, on peatland development are poorly understood. Timescales of monitoring studies in ditch‐drained and restored peatlands are typically limited to a few years, and occasionally decades. In addition, experimental studies seldom monitor spatial changes in peat structure caused by ditches, despite such changes affecting water flow and water retention in peat. Ecosystem models offer an alternative to experimental studies and can help explain how complex systems such as peatlands may respond to external disturbances. Here we report on a 2‐D application of a peatland development model (DigiBog) to explore how contour‐parallel ditches, and their damming, affect the ecohydrology of peatlands over decades to centuries, using blanket peatlands as a case study. Drainage resulted in the rapid loss of peat due to increased oxic decay. The majority of these losses occurred in the first 100 years after the ditch was created, but water table dynamics were altered even centuries later. Restoration halted the loss of peat and encouraged net peat accumulation, although the amount lost in 100 years of drainage had not been replaced 200 years after the ditch was dammed. Restoration of ditches in sloping peatlands brought about more peat regrowth downslope of the restored ditch than further upslope. Our study demonstrates the potential for spatially distributed ecosystem‐scale models as tools to explore complex spatiotemporal responses to disturbance, and to support land managers in making decisions about peatland drainage and restoration. Plain Language Summary: Peatlands are globally important stores of carbon, but many have been drained either artificially or because of gully systems. Drainage can destabilize the carbon stored in peatlands and as a result damming of drainage features has become widespread in peatland restoration. However, studies that monitor peatland drains and their restoration are often limited to a few years, or occasionally decades, and the longer‐term effects on peatlands is poorly understood. We report on the use of a peatland model to explore how drains, and their damming, affect the ecohydrology of peatlands over timescales of decades to centuries. Drainage resulted in the rapid loss of peat due to increased decomposition. Most losses occurred in the first 100 years after the drain was created, and water table dynamics were altered even centuries later. Restoration halted the loss of peat and encouraged peat to accumulate, although the amount lost in 100 years of drainage had not been recovered 200 years after the drain was dammed. Peat regrowth downslope of the restored drain was more pronounced than further upslope. Our study demonstrates the potential for models to be used to explore complex responses to disturbance, and to support land managers in making decisions about peatland drainage and restoration. Key Points: Drainage causes lasting changes to simulated peat structure depending on proximity to a drainage ditch and up or downslope position Drainage affects long‐term simulated peat accumulation before and after ditch damming altering the developmental trajectory of a peatland Ecosystem models can complement field observations with insights into how peatlands respond to drainage and restoration over centuries